Польсько-латинський макаронізм і «слов’яноруська» мова - Кисельов, Р. (Слово і Час, 2022)
Предметом статті є генеза українсько-церковнослов’янського гібридного
мовлення, популярного в кінці XVII—XVIII ст., та підстави його поширення в літературі. На думку автора, звернення до церковнослов’янської мови як до релігійно-культурного маркера, що має статусні переваги, не
було основним і незалежним чинником у розвиткові цієї практики. Так
само не мав вирішального значення російський вплив. Найбільше стимулював т. зв. слов’яноруську мову саме латинсько-польський мовний макаронізм, який і завдяки традиції послуговуватися таким типом мовлення,
і через освіту був закріплений у суспільній свідомості як норма. А отже,
творення гібридних українсько-церковнослов’янських текстів було для
українців ще одним способом реалізації своєї-таки розумової звички, виробленої регулярним використанням польсько-латинської мовної суміші. The paper focuses on the genesis of Ukrainian-Church Slavonic hybrid language, popular at
the end of the 17th and during the 18th century among Ukrainian writers. Usually, this new
love for the Church Slavonic, which led to the emergence of a hybrid literary form, is explained
by two factors: piety to the Church Slavonic and the influence of Russian tradition,
where the practice of mixing Church Slavonic with the vernacular was stable and almost
unalterable. According to the paper’s author, the use of Church Slavonic as a religious and
cultural marker, which had status advantages, was not a major and independent factor in the
development of this practice. The poor knowledge of Church Slavonic in society and the
lack of eff orts to learn it, even among priests, undermine the notion that the sacralization of
this language could lead to the creation of hybrid forms by itself. The Russian infl uence was
not crucial as well, which is confi rmed, in particular, by the proliferation of similar language
use in the Right Bank Ukraine, free from tendencies of russifi cation. The so-called ‘slovianoruska
mova’ (Slavonic-Ruthenian language) was stimulated above all by the Latin-Polish
macaronic mix, which, due to the local tradition of using such a language, and, importantly,
through education, has been established in the public consciousness as a norm. The rhetoric
courses and the practice of delivering occasional orations in Polish ensured the development
of the trend. Therefore, both in Ukraine under Russian rule and in the Right Bank Ukraine
within the Polish-Lithuanian Commonwealth, the creation of hybrid Ukrainian-Church
Slavonic texts was just another way of actualizing one’s mental habit, produced by the regular
use of the Polish-Latin language mixture.